(Butane-1,3-diyne-1,4-diyl)bis(triisopropylsilane) - Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
The molecule of the title compound, C(22)H(42)Si(2), lies on a center of inversion, and the triisopropylsilyl groups are staggered